Mining Royalties : A Global Study of Their Impact on Investors, Government, and Civil Society - Otto, James (Washington, DC: World Bank, 2012)
Mineral sector regulatory and fiscal systems have been undergoing major reforms across the globe. This book focuses on information and analysis relating to mineral royalties. It provides a general discussion of the concepts behind mining taxation, a guide to royalties, examples of royalty calculations and the ways in which these interact with other forms of taxation, as well as financial effects on investments under varying conditions. Primary information includes royalty legislation from over forty nations. The book discusses implications for investors and governments of various tax regimes and provides specific country case examples. A chapter is included on transparency, governance, and management of revenue streams. The appendices, in the second volume, contain brief summaries and selected statutes relating to royalties in a broad cross-section of nations around the world; sample spreadsheets of the results of mine models that were analyzed; and examples of administrative and distributional approaches to collecting royalties.